2021
DOI: 10.1038/s41598-021-01529-3
|View full text |Cite
|
Sign up to set email alerts
|

Piperine analogs arrest c-myc gene leading to downregulation of transcription for targeting cancer

Abstract: G-quadruplex (G4) structures are considered a promising therapeutic target in cancer. Since Ayurveda, Piperine has been known for its medicinal properties. Piperine shows anticancer properties by stabilizing the G4 motif present upstream of the c-myc gene. This gene belongs to a group of proto-oncogenes, and its aberrant transcription drives tumorigenesis. The transcriptional regulation of the c-myc gene is an interesting approach for anticancer drug design. The present study employed a chemical similarity app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 137 publications
0
7
0
Order By: Relevance
“…12 To find new promising pesticide candidates, recently, structural modification of natural bioactive products has received much attention. 13−15 Piperine (1, Figure 1) as a natural alkaloid isolated from the black pepper (Piper nigrum), exhibited a variety of biological properties including anticancer, 16,17 anti-inflammation, 18 anti-Alzheimer's disease (AD), 19 anti-Parkinson's disease (PD), 20,21 antiseizure, 22 antiadipogenic, 23 and insecticidal activities. 24−27 Previously, we found that the ester group can play a key role for improving agrochemical activities, for instance, some of osthole esters (I and II, Figure 1), 28,29 andrographolide esters (III, Figure 1), 30 and limonin esters (IV, Figure 1) 31 showed interesting pesticidal activities.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 To find new promising pesticide candidates, recently, structural modification of natural bioactive products has received much attention. 13−15 Piperine (1, Figure 1) as a natural alkaloid isolated from the black pepper (Piper nigrum), exhibited a variety of biological properties including anticancer, 16,17 anti-inflammation, 18 anti-Alzheimer's disease (AD), 19 anti-Parkinson's disease (PD), 20,21 antiseizure, 22 antiadipogenic, 23 and insecticidal activities. 24−27 Previously, we found that the ester group can play a key role for improving agrochemical activities, for instance, some of osthole esters (I and II, Figure 1), 28,29 andrographolide esters (III, Figure 1), 30 and limonin esters (IV, Figure 1) 31 showed interesting pesticidal activities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Piperine ( 1 , Figure ) as a natural alkaloid isolated from the black pepper (Piper nigrum), exhibited a variety of biological properties including anticancer, , anti-inflammation, anti-Alzheimer’s disease (AD), anti-Parkinson’s disease (PD), , antiseizure, antiadipogenic, and insecticidal activities. Previously, we found that the ester group can play a key role for improving agrochemical activities, for instance, some of osthole esters ( I and II , Figure ), , andrographolide esters ( III , Figure ), and limonin esters ( IV , Figure ) showed interesting pesticidal activities. In addition, the Vilsmeier–Haack–Arnold (VHA) reaction has frequently been used in the total synthesis of natural products and drugs, and its main function includes aromatic formylation reaction or as a fulcrum for the introduction of different functional groups to obtain target compounds, such as homofascaplysin C and commercial anticarcinogen Sunitinib malate. , Consequently, in this paper we wanted to prepare a series of new piperine-type ester derivatives via the key intermediate aldehyde by application of a VHA formylation reaction of piperine (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…The aberrantly expressed c-Myc, a member of MYC gene family, has been proved to participate in the regulation of multiple biological functions in human cancers 31 . It has been reported that c-Myc could regulate the transcription of targeted genes by binding some histone components 32 . Amente et al showed that c-Myc could directedly bind and recruit KDM1A to the E-box chromatin, promoting the transcriptional activity of target genes 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Compound 4 ( Figure 2 ) exhibited powerful inhibitory activity with a half-maximal inhibitory concentration (IC 50 ) value of 231 nM [ 37 ]. Pandya et al found that piperine analogue 5 ( Figure 2 ) may serve as an anticancer therapeutic seeing it affects c-myc oncogene expression via G-quadruplex mediated mechanism [ 38 ].…”
Section: Bioactivities Of Piperine and Its Derivativesmentioning
confidence: 99%
“…The SARs analysis of piperine and its derivatives are described in Figure 6 , and the detailed descriptions are as follows: (i) introduction of hydroxyl groups at C-8 and C-9 positions can obtain a potent antiviral candidate [ 38 ]. Replacing the dioxymethylene ring with a 2-oxazoline heterocyclic ring and introducing a Cl atom at the C-10 position can produce an anti-inflammatory agent, which has potent therapeutic effects against neuroinflammation [ 46 ]; (ii) introduction of ester and oxime ester groups at C-2 position of piperine is important for improving acaricidal activity.…”
Section: Structure-activity Relationships Of Piperine and Its Derivat...mentioning
confidence: 99%